Pengaruh Energi Terbarukan dan Adopsi Teknologi Terhadap Kualitas Udara Negara Berkembang di Asia Tenggara - Joan Marta; Iing Aprilia Laura (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to determine and analyze how renewable energy and technology adoption affect air quality in developing countries in Southeast Asia. This study uses secondary data sourced from the World Bank from 2000-2021 with research variables grouped into three parts: the dependent variable which in this study is defined as air quality, and the independent variables are renewable energy and technology adoption, and the control variables used in this study are economic openness, manufacturing sector, Gross Domestic Product (GDP), forest area and energy intensity. This study uses panel data regression analysis with a cross section of 5 developing countries in Southeast Asia and a time series from 2000-2021. The results of the study indicate that renewable energy and technological adoption have a negative effect on air quality as measured by carbon dioxide (CO2) emission levels, thus providing an opportunity to reduce carbon dioxide (CO2) emission levels in these countries.